Terahertz emission characteristics of GaMnAs dilute magnetic semiconductor under 650 mT external magnetic field - De Los Reyes, Alexander (Animo Repository, 2017)
We investigate the effects of an externally applied magnetic field on the terahertz (THz) emission of Gallium Manganese Arsenide (GaMnAs) films grown via molecular beam epitaxy (MBE). Results show that low Mn-doping in GaMnAs resulted to increased THz emission as compared with a SI-GaAs substrate. Further increase in Mn-doping content resulted to a comparably less THz emission, which is attributed to reduced crystallinity and higher free-carrier absorption. Under an external magnetic field, the contributions of the Bup and Bdown-related THz emission were observed to be asymmetric: possibly due to intrinsic magnetic properties of GaMnAs.